Structural, microstructure, optical, and dielectric properties of Sr1.99M0.01SnO4 (M: La, Nd, Eu) Ruddlesden–Popper oxide - Kumar U.; Upadhyay S. (My University, 2025)
This manuscript deals with the structural and optical properties of Sr1.99M0.01SnO4 (M: La, Nd, Eu). The single phase of the compositions is prepared by a conventional ceramic route followed by calcination at 1000 °C for 8 h. The lattice parameters determined from Rietveld refinement indicate that it gradually increases with doping of La to Eu. Microstructural analysis of the samples has been analyzed using scanning electron microscopy (SEM) and found that Nd3+ and Eu3+ act as grain growth promoters and La3+ as grain growth inhibitor. However, energy-dispersive X-ray (EDX) analysis shows the compositional homogeneity of the surface of samples. The absorption spectrum of the samples suggests that it is optically active in the UV region but transparent from the visible to IR region. The direct and indirect bandgap values of the samples are follow similar trend as lattice parameters because of the lower ionic radii of dopant. Urbach energy of the samples has been calculated from absorption data, which gradually increases with the dopant concentration except for Nd3+. The dielectric constant and dissipation factor of the samples are found to be in the range of 167–240 and 0.01–0.68, respectively. By utilizing these optical states as a metastable state, it can be used in UV detector, semiconductor devices, and optoelectronic device applications. The dielectric properties of samples make it a promising candidate for high frequency-based devices and dielectric capacitor application. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.